2001
DOI: 10.1023/a:1012304710187
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The role of nitric oxide (NO) synthase inhibitors in indomethacin (INDO) -induced enteropathy was investigated in male Sprague-Dawley rats. Rats were subcutaneously administered 5% sodium bicarbonate (controls), two doses of INDO 7.5 mg/kg, and three different inducible NO synthase (iNOS) inhibitors at various concentrations 24 hr, apart; aminoguanidine (AG), guanidinoethyldisulfide (GED), and n-(3-aminomethyl)benzylacetamidine (1400W). Rats were killed four days after the initial injection and small intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…45) NOx production is a contributing factor in the pathogenesis of enteropathy. 31,32,46,47) It has been reported that the iNOS is closely related to the development of intestinal microvascular injury induced by indomethacin. 47) OGT influences microcirculatory blood flow, which is one of the mechanisms responsible for the efficacy of OGT.…”
Section: Fig 10 Localization Of Cox-2 Expressing Cellsmentioning
confidence: 99%
“…45) NOx production is a contributing factor in the pathogenesis of enteropathy. 31,32,46,47) It has been reported that the iNOS is closely related to the development of intestinal microvascular injury induced by indomethacin. 47) OGT influences microcirculatory blood flow, which is one of the mechanisms responsible for the efficacy of OGT.…”
Section: Fig 10 Localization Of Cox-2 Expressing Cellsmentioning
confidence: 99%